Optimalisasi Dosis Pupuk Organik Cair Mikroorganisme Lokal Terhadap Pertumbuhan Sawi Daging - Kustiani, Edy; Saptorini, Saptorini (Kadiri University, 2019)
Liquid organic fertilizers are biological fertilizers which are made through a process of decomposition to produce liquid which acts as a nutrient needed for plants. Local microorganism liquid organic fertilizer (MOL) is a liquid produced from natural resources available in the place where MOL is made, containing macro, micro and microbial nutrients that function as decomposition or decomposition. The object of research is the mustard plant which is a vegetable plant (olericulture) so it is very suitable for development because, the direction from after harvesting is for consumption, both personally and society at large. This research was conducted in the greenhouse of the Faculty of Agriculture, Kadiri University, Kediri from September to October 2017. The environmental design used was a completely randomized design (CRD) with a factorial treatment design consisting of two factors, namely; the first factor was the composition of the planting medium and the second factor was the liquid organic fertilizer MOL. Based on the results of observations and analysis of variance, it can be seen that there is no interaction between the treatment of the composition of the growing media and the dosage of MOL liquid organic fertilizer on plant height at all observation ages. In the best media composition treatment, compost: 1: 1 manure showed the best results. Treatment of local microorganism liquid organic fertilizer (MOL) at a dose of 5cc / pot showed the best results.Pupuk organik cair adalah pupuk hayati yang dibuat melalui proses pembusukan sehingga menghasilkan cairan yang berperan sebagai unsur hara yang dibutuhkan untuk tanaman. Pupuk organik cair mikroorganisme local (MOL) adalah cairan yang dihasilkan dari sumber daya alam yang tersedia di tempat pembuatan MOL, mengandung unsur hara makro, mikro juga mikroba yang berfungsi sebagai perombak atau pendekomposisi. Adapun objek penelitian adalah tanaman sawi daging yang merupakan tanaman sayuran (olerikultura) sehingga sangat cocok pengembanganya karena, arah dari setelah panen adalah untuk konsumsi, baik pribadi maupun masyarakat luas. Penelitian ini dilakukan di rumah kaca Fakultas Petanian Universitas Kadiri, Kediri mulai bulan September dengan Oktober 2017. Rancangan lingkungan yang digunakan adalah Rancangan Acak Lengkap (RAL) dengan rancangan perlakuan faktorial yang terdiri dua factor yaitu; faktor pertama adalah komposisi media tanam dan faktor kedua adalah pupuk organik cair MOL. Berdasarkan hasil pengamatan dan analisis ragam dapat diketahui bahwa tidak terjadi interaksi antara perlakuan komposisi media tanam dengan dosis pupuk organik cair MOL terhadap tinggi tanaman pada semua umur pengamatan. Pada perlakuan komposisi media terbaik kompos:pupuk kandang 1:1 menunjukkan hasil terbaik. Perlakuan dosis pupuk organik cair mikriorganisme lokal (MOL) dosis 5cc/pot menunjukkan hasil terbaik.